A training and development project to improve services and opportunities for social inclusion for children and young people with autism in Romania. (October 2014) - Pasco, Greg; Clark, Bruce; Dragan, Ioana; Kalambayi, Fidelie; Slonims, Vicky; Tarpan, Adelaide Katerine; Wittemeyer, Kerstin
In 2010, the Romanian Angel Appeal Foundation launched a 3-year national training and development programme to develop and deliver a model of diagnostic and therapeutic services aimed at promoting social inclusion for children and young people with autism spectrum disorders. The project adopted a number of strategies aimed at developing knowledge and skills among professionals and increasing awareness in political and public spheres: (a) a three-stage training programme designed to increase knowledge of autism spectrum disorders and promote best practice among professionals working in services providing for children with autism spectrum disorders and their families, on a nationwide basis; (b) two online courses for general practitioners and psychiatrists, with content relating to the identification, diagnosis and treatment of autism spectrum disorders; (c) a total of 40 counselling and assistance centres for people with autism spectrum disorders were launched in partnership with local authorities; (d) a national strategy for social and professional integration of people with autism spectrum disorders developed through consultation with political, statutory and voluntary sector partners; and (e) a nationwide media campaign to raise awareness of the needs of children and young people with autism spectrum disorders that reached over eight million people. The project provides a transferable model to achieve important improvements in the quantity and quality of services on a national level within a brief time frame.